2016
DOI: 10.1016/j.beproc.2016.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Self-control assessments of capuchin monkeys with the rotating tray task and the accumulation task

Abstract: Recent studies of delay of gratification in capuchin monkeys using a rotating tray (RT) task have shown improved self-control performance in these animals in comparison to the accumulation (AC) task. In this study, we investigated whether this improvement resulted from the difference in methods between the rotating tray task and previous tests, or whether it was the result of greater overall experience with delay of gratification tasks. Experiment 1 produced similar performance levels by capuchins monkeys in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 76 publications
1
17
0
Order By: Relevance
“…Few studies have explored whether delayed gratification is consistent within an individual when tested using different paradigms. In capuchins, individuals tested on the rotating tray and accumulation paradigm were more proficient on the rotating tray than accumulation task (Evans et al 2012), and also showed improved self-control overall likely due to greater experience of delayed gratification tasks (Beran et al 2016a). Future studies could similarly compare delay of gratification paradigms, including the rotating tray with other paradigms, with one another within the same sample and species, which, to our knowledge, has yet to be done with most species, including New Caledonian crows and children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have explored whether delayed gratification is consistent within an individual when tested using different paradigms. In capuchins, individuals tested on the rotating tray and accumulation paradigm were more proficient on the rotating tray than accumulation task (Evans et al 2012), and also showed improved self-control overall likely due to greater experience of delayed gratification tasks (Beran et al 2016a). Future studies could similarly compare delay of gratification paradigms, including the rotating tray with other paradigms, with one another within the same sample and species, which, to our knowledge, has yet to be done with most species, including New Caledonian crows and children.…”
Section: Discussionmentioning
confidence: 99%
“…In the exchange paradigm, subjects may be required to swap rewards or tokens with an experimenter or conspecific to acquire the 'better' reward (Beran et al 1999). In the accumulation paradigm, rewards accumulate at a steady rate within the subject's reach until they touch or consume them (Beran et al 2016a). These and other delayed gratification paradigms have been used to test self-control in a number of species, including non-human primates, corvids and parrots, typically in single-species studies.…”
Section: Introductionmentioning
confidence: 99%
“…higher uncertainty) lead individuals towards more conservative decisions. Similarly, some studies have shown that chimpanzees and other primates such as capuchins ( Sapajus apella ) can wait more than 20 seconds (and even up to several minutes) to obtain preferred rewards while refusing less valuable options [32, 33]. Chimpanzees can also wait for partners to engage in mutual collaboration [34] but competitive scenarios, such as the one presented here, may hinder the ability to inhibit prepotent responses: chimpanzees need to divide their attention across different inputs within a limited amount of time (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In accumulation tasks, food items accumulate at a steady rate within subject reach until they touch or begin to consume them (Beran, Perdue, et al, ). Thus, there is a trade‐off between how long the animal waits to start eating, and the total amount of reward.…”
Section: Delay Of Gratification Tasks and Performancementioning
confidence: 99%